Studies of microscopic nonequilibrium stochastic dynamics in optical tweezers - Martins, Thalyta Tavares (2024)
This thesis addresses the development of studies on stochastic thermodynamics using optical tweezers, ranging from classical to quantum regimes. Initially, the application of outof- equilibrium processes is explored with Brownian particles, and their thermodynamic quantities are computed through trajectories obtained from an ensemble of realizations. Microscopic thermodynamic laws and fluctuation theorems, such as Jarzynskis equality and Crookss relation, are checked by implementing compression and expansion protocols via beam intensity control. The results show good agreement with theoretical expectations and our experimental systems robustness. Subsequently, experimental verification of optimal protocols (minimizing the average dissipated work) for trap compression and simulations for moving potentials are demonstrated. The experiments revealed the best energetic efficiency of optimal processes, i.e. they presented lower average work than linear (suboptimal) ones, which is consistent with the analytical solution. Towards efficient protocols, a feedback system was implemented for converting information to energy inspired by Maxwells demon idea. Despite experimental challenges, feedback protocols returned lower average work values than those with no feedback, and efficiency can be explored by altering the demons criteria. Finally, initial results are provided aiming at explorations of stochastic thermodynamics at the classical-quantum interface through investigation of trapped optically active particles (formed by quantum dots). The analysis of the particle recoil revealed that Langevin dynamics must be extended to describe our system precisely.